Space-time clustering of childhood cancer around the residence at birth - McNally, R; Bithell, J; Vincent, T; Murphy, M (Wiley-Liss, 2009)
Previously, we identified space-time clustering in certain childhood cancers around diagnosis residence. These findings provided support for the involvement of environmental agents in etiological processes occurring close to diagnosis. We have reanalyzed the same British population-based dataset. The aim of the study was to determine whether there was space-time clustering around the residence at birth in relation to time of birth and separately from time of diagnosis. A total of 29,553 cases, diagnosed during the period 1969-1993, were examined by a second-order procedure based on K-functions. Locations were birth addresses, but separately, both dates of birth and diagnosis were analyzed. There was statistically significant space-time clustering for Hodgkin lymphoma (HL) and central nervous system (CNS) tumors (p = 0.047 and 0.01, respectively, based on birth date) and for total leukemia at ages 1-4 years only, Non-Hodgkin lymphoma (NHL) and Wilms tumor (p = 0.01, 0.02 and 0.006, respectively, based on diagnosis date). These results, interpreted together with other epidemiological evidence, suggest an etiological role for environmental factors focused around birth address for certain childhood cancers. For HL and CNS tumors, findings suggest that etiological exposures occurred at similar ages or in utero. For leukemia, NHL and Wilms tumor there is support for exposures occurring at similar times before diagnosis. For leukemia, HL, NHL and CNS tumors, but not Wilms tumor, the findings are consistent with infectious hypotheses.